2021
DOI: 10.1186/s40563-020-00131-6
|View full text |Cite
|
Sign up to set email alerts
|

Adhesively bonded joints of jute, glass and hybrid jute/glass fibre-reinforced polymer composites for automotive industry

Abstract: Natural fibre-reinforced composites have attracted a great deal of attention by the automotive industry mainly due to their sustainable characteristics and low cost. The use of sustainable composites is expected to continuously increase in this area as the cost and weight of vehicles could be partially reduced by replacing glass fibre composites and aluminium with natural fibre composites. Adhesive bonding is the preferred joining method for composites and is increasingly used in the automotive industry. Howev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
29
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 50 publications
(30 citation statements)
references
References 38 publications
0
29
0
1
Order By: Relevance
“…Natural fiber reinforced polymer composites have demonstrated outstanding potential for many different applications in various industries such as automotive, domestic furniture, food packaging, and agricultural industry [7,[9][10][11]. The growing importance of natural fiber reinforced composites is reflected by the increasing number of publications (e.g., reviews, patents, book chapters and books) during the recent years [12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Natural fiber reinforced polymer composites have demonstrated outstanding potential for many different applications in various industries such as automotive, domestic furniture, food packaging, and agricultural industry [7,[9][10][11]. The growing importance of natural fiber reinforced composites is reflected by the increasing number of publications (e.g., reviews, patents, book chapters and books) during the recent years [12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…However, nowadays, the industry is seeking new desirable characteristics of composite materials, such as renewability, eco-friendliness, and low cost. Consequently, there has been great interest in research and innovation in natural fiber composites owing to the advantages of these materials compared to their synthetic fiber counterparts (i.e., lower environmental impact and lower cost), supporting their potential across a wide range of applications in several industrial sectors [4][5][6][7][8][9]. The natural fiberreinforced composites (NFRCs) are used mainly in non-structural car body parts, such as door panels, package trays, hat racks, instrument panels, internal engine covers, sun visors, boot liners, oil air filters, and even progressing to more structurally demanding parts, such as seat backs and exterior underfloor paneling [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…e studies attributed this observation to the addition of high-strength glass fibres to jute fibres [10,139]. Further review literature has reported lower tensile, impact, flexural, and interlaminar shear strengths for glass/jute reinforced hybrid composites compared to glass fibre reinforced polymer composites.…”
Section: Jute/glass Fibre Reinforced Polymer Hybrid Compositesmentioning
confidence: 99%
“…In contrast, natural fibre reinforced composites are characterized by low weight, low cost, renewability, biodegradability, and high specific mechanical properties. In addition, natural fibre reinforced composites are perceived to be carbon neutral and environmental-friendly [10][11][12][13]. Natural fibre reinforced composites are used in various nonstructural automobile applications such as door panels, internal engine covers, boot liners, oil filter liners, package trays, instrument panels, and oil air filters, amongst others [7].…”
Section: Introductionmentioning
confidence: 99%